On the Socio-Sexual Behaviour of the Extinct Ursid Indarctos arctoides: An Approach Based on Its Baculum Size and Morphology - Abella, Juan; Valenciano, Alberto; Pérez-Ramos, Alejandro; Montoya, Plinio; Morales, Jorge (PLOS ONE, 2013)
The fossil bacula, or os penis, constitutes a rare subject of study due to its scarcity in the fossil record. In the present paper we describe five bacula attributed to the bear Indarctos arctoides Depéret, 1895 from the Batallones-3 site (Madrid Basin, Spain). Both the length and morphology of this fossil bacula enabled us to make interpretative approaches to a series of ecological and ethological characters of this bear. Thus, we suggest that I. arctoides could have had prolonged periods of intromission and/or maintenance of intromission during the post-ejaculatory intervals, a multi-male mating system and large home range sizes and/or lower population density. Its size might also have helped females to choose from among the available males.